Dynamical Behaviors of the Stochastic Hopfield Neural Networks with Mixed Time Delays - Li Wan; Qinghua Zhou; Zhigang Zhou; Pei Wang (Abstract and Applied Analysis)
This paper investigates dynamical behaviors of the stochastic Hopfield neural networks with mixed time delays. The mixed time delays under consideration comprise both the discrete time-varying delays and the distributed time-delays. By employing the theory of stochastic functional differential equations and linear matrix inequality (LMI) approach, some novel criteria on asymptotic stability, ultimate boundedness, and weak attractor are derived. Finally, a numerical example is given to illustrate the correctness and effectiveness of our theoretical results.